(Invited) Innovative Embedded Non-Volatile Memories: Flexibility and Reliability. (14th September 2015) - Navarro, Gabriele; Vianello, Elisa; Molas, Gabriel; Sousa, Véronique; Perniola, Luca
Abstract : Innovative non-volatile memory technologies promise high performance and low integration cost with respect to conventional Flash memory, in a market context where the demand of data storage is constantly increasing and the portfolio of possible applications is rapidly widening. Non-Volatile Resistive Memory NVRM (e.g. Phase-Change Memory, Oxide-based Memory and Conductive Bridging Memory) is rapidly increasing in maturity, and it can represent a real breakthrough in terms of performances, power consumption lowering and cost reduction. Since flexibility and reliability are among the key words of the actual and future semiconductor memory scenario, we present some of the features of the main NVRM technologies and how target specifications can be satisfied by materials tuning, architecture engineering and specific programming techniques.